Definição de processos baseada em componentes - Segrini, Bruno Marques (2009)
It is known that software product quality depends on the quality of the software processes used in its development and maintenance. However, defining software processes is not a trivial task, being necessary knowledge, experience and support approaches, aiming to reduce the effort required to carry it out. In this work, a Component-Based Process Definition (CBPD) approach was defined. It uses some concepts and makes analogies to the Component-Based Development (CBD), with the goal of facilitating the processes definition task. In this approach, the software process definition in an organization is performed through the composition of pre-existing process components, being possible to define standard processes and project-specific processes. This work also includes the evolution of the software process definition tool of ODE (Ontology-based software Development Environment), a Process-Centered Software Engineering Environment based on ontologies. This evolution aims to provide automated support to the process definition task, now considering process component composition.